Istiochrysis gen. nov., a new chrysidid genus from Oriental China (Hymenoptera, Chrysididae) - Rosa, Paolo; Feng, Jun; Xu, Zai-Fu (Zootaxa, 2016)
Istiochrysis Rosa & Xu, gen. nov. (type species Istiochrysis ziliolii Rosa, Feng & Xu, sp. nov.) in the tribe Chrysidini is described from Oriental part of China (Yunnan). The new genus is related to the genera Caenochrysis Kimsey & Bohart, 1981, Chrysidea Bischoff, 1913, and Trichrysis Lichtenstein, 1876, but can be separated from them by the unique crestate structure of male genitalia, shape of black spots on sternum 2, and facial depressions on scapal basin.